IMPACT OF INSULIN OR INSULIN LIKE GROWTH FACTOR-I ADMINISTRATION DURING MID-LUTEAL PHASE OF ESTROUS CYCLE ON IN VIVO EMBRYO PRODUCTION IN SAHIWAL CATTLE - SHEETAL, S K; PRASAD, S; GUPTA, H P (The Indian Journal of Animal Reproduction, 2022)
On day 5, 6, 7, and 8 (mid-luteal phase) of estrous cycle, two groups of Sahiwal cattle were administered(S.C.) insulin (n=6) or IGF-I (n=6), whereas, another group was kept as untreated control (n=6). The embryoswere collected non-surgically on day 7 of superovulatory estrus. In all the groups, the maximum diameter (mm)of largest follicle and 2nd largest follicle was recorded on day 13 of estrous cycle. The number of ovulations,recovered total embryo/ova, transferable embryos, degenerated embryos and unfertilized ova differed (p>0.05)between groups. Insulin-treated cattle had highest (p>0.05) number of total embryo, transferable embryo andrecovered blastocyst. In brief, insulin administration during mid-luteal phase of estrous cycle has the potential toimprove in vivo embryo production in Sahiwal cattle.
Keywords: Blastocyst; Embryo; IGF-I, Insulin; Sahiwal; Superovulation